A case of Behcet’s disease with upper extremity thrombosis - Albay, Ayşegül; Kanatsız, Büşra; Platin, Ayşe Rana; Sali Çakır, Hacer; Oludağ, Gülay; Basat, Sema (Journal of Surgery and Medicine, 2018)
Behcet’s disease (BD) is a multi-system vasculitis in which recurrent oral and genital ulcers, uveitis as well as musculoskeletal, neurologic and gastrointestinal system involvement are observed. In previous studies, vascular involvement rate ranges between 1-38%. Most common vascular complication is superficial vein thrombosis of the extremities, followed by deep vein thrombosis. In this study, we will present a case of BD with upper extremity thrombosis.